VIABAHN® Stent Graft Implantation for Iatrogenic Arteriovenous Fistula and Pseudoaneurysm of the Deep Femoral Artery - Daisuke Yamazaki; Takahide Fujihashi; Hirokazu Amamizu; Tomoka Kobayashi; Toru Takahashi (Case Reports in Cardiology)
Femoral arteriovenous access is most commonly used in endovascular diagnosis and treatment. Complications arising during femoral arteriovenous access include hematoma, retroperitoneal hemorrhage, pseudoaneurysm, and arteriovenous fistula. A 66-year-old woman diagnosed with paroxysmal atrial fibrillation was treated with catheter ablation. This patient had a high femoral artery bifurcation, and we punctured the femoral vein by the conventional Merkmal method, which led to a femoral vein puncture through the deep femoral artery. The next day, echography revealed a pseudoaneurysm communicating with the deep femoral artery. We performed a thrombin injection without complication, and the pseudoaneurysm was occluded. However, echography three days after thrombin embolization showed a recurrence of the pseudoaneurysm and an arteriovenous fistula connecting to the common femoral vein. The first choice for the treatment of pseudoaneurysms and arteriovenous fistula is surgical treatment, but in addition to the lack of vascular surgery in our hospital, the patient did not want an invasive treatment and strongly preferred to be treated with a catheter. We performed endovascular treatment by VIABAHN® stent graft insertion. VIABAHN® stent graft was implanted at the deep femoral artery, and the patient was discharged without complications. VIABAHN® stent graft placement in the deep femoral artery sealed the entrance of the pseudoaneurysm and the arteriovenous fistula at once, which simultaneously treated both the pseudoaneurysm and AV fistula, and helped avoid the use of an invasive surgical procedure.